A Rational Critique of the Progressive Islamic Methodology - Hendar Riyadi (UIN Sunan Gunung Djati Bandung, 2026)
This research proposes shifting the bayani-burhani-irfani approach to bayani-burhani-maqâsidi. The intellectual history of Muhammadiyah cannot be separated from the methodological dialectic that underlies its movement. One of the most important methodological products that has always served as the basis for ijtihad in the movement's thought and practice is the Manhaj Tarjih and the Development of Islamic Thought. This Manhaj Tarjih offers three approaches to understanding religious teachings: bayani, burhani, and irfani. These three approaches are established as Islamic ways of thinking and form the Manhaj of Progressive Islam. However, since their formulation, these three approaches have been quite controversial. Some scholars consider this Manhaj Tarjih a manifesto of the modernist thought renewal movement in Indonesia. Others, not a few, view it negatively and pejoratively as a liberal method. Moreover, the irfani method is identical to Sufism and is procedurally difficult to operationalize. This paper aims to conduct a rational critique or epistemological evaluation of the Manhaj Tarjih and the Manhaj of Progressive Islam. The argument in this paper is the need for re-examination and re-investigation (conducting a rational critique) of the Manhaj Islam Berkemajuan and Manhaj Tarjih, which are the foundation of its approach. Based on the conclusive description method and discourse analysis techniques, this paper concludes that the bayani, burhani, and irfani approaches need to reconstruct their basic assumptions and methodological steps. The proposal to include integralistic assumptions, the hierarchy of norms and intentions, and the istiqra` ma'nawi method is very relevant. In this regard, this paper proposes to shift the bayâni-burhâni-irfâni approach to bayâni-burhâni-maqâsidi.